The effect of the STM tip on Si(100) reconstructed surfaces - Ramos, Marta M. D. (1993)
We present a theoretical study of the effects of the STM tip on the geometry of Si(100) reconstructed surfaces. The energy barrier to switching between different reconstructions is also discussed. We use a molecular dynamics method and self-consistent forces to simulate the time-dependent behaviour of the surface atoms. The molecular orbital calculations are performed at the CNDO level using a cluster model. Our results indicate significant differences for positively and negatively biased tips. The thermally induced rocking of surface dimers is inhibited by the application of a positive bias to the tip and it is promoted by a negative bias. These bias-dependent effects may offer a plausible explanation for the bias dependence of STM images of this surface.